Combating aflatoxin contamination by combining biocontrol application and adapted maize germplasm in northeastern and southeastern Mexico - Muñoz-Zavala, Carlos; Molina Macedo, Aide; Toledo, Fernando H.; Telles Mejía, Eugenio; Cabrera-Soto, Luisa; Palacios-Rojas, Natalia (Elsevier, 2025)
Maize is highly vulnerable to aflatoxin (AF) contamination caused by fungi from the Aspergillus section Flavi, with deficiencies in post-harvest management practices further exacerbating AF levels. Due to their carcinogenic properties, AFs pose significant health risks. Biological control using non-aflatoxigenic A. flavus isolates has been effective for over 25 years in the USA, with two formulations being commercially available. However, no such products have been developed yet for use in Mexico. This study evaluated the effectiveness of AF36-Prevail®, a non-aflatoxigenic strain from Arizona, for reducing aflatoxin contamination in Mexico. Over four years (2019–2022), we assessed its impact alongside regionally adapted maize germplasm in northeastern and southeastern Mexico. We analyzed a total of 1,479 grain samples, with 887 from biocontrol-treated fields, and 592 from untreated fields across 69 sites in Tamaulipas and Campeche. Treated fields showed 59.0 % to 89.9 % reductions in AF content compared to untreated fields, and higher ear rot was observed in untreated fields. Correlation coefficients between ear rot and AF content were r = 0.08 for Campeche and r = 0.36 for Tamaulipas. Significant differences (p ≤ 0.001) were noted between years and hybrids for both yields and AF levels. Three hybrids in Tamaulipas and four in Campeche demonstrated better adaptation, higher yields, and lower AF levels (< 20 ppb). This research underscores the potential for safer maize production in Mexico, particularly when combining biocontrol strain application with adapted germplasm.